MEDIA PEMBELAJARAN TLJ MENGGUNAKAN SMART APPS CREATOR PADA MATERI KOMUNIKASI DATA DI SMK - Nopian Siswahyudi; Purnamawati; Abdul Muis Mappaloteng (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This research is a development research with the ADDIE approach model through 5 stages, including:(1) Analysis, (2) Design, (3) Development, (4) Implementation (5) Evaluation. Expert validation was carried out by two media experts. The test subjects were teachers and students. The trials carried out included two stages, namely small-scale trials and large-scale trials. The data collection technique in this study was using a questionnaire, the quantitative data obtained was then analyzed using statisticsdescriptive.The results of the study show that: (1) Learning media products based on SAC 3 in TLJ subjects for SMK students in Enrekang Regency are appropriate to use. (2) The product feasibility level based on the media expert's assessment averaged 85.67%, included in the very feasible category. (3) Based on the effectiveness test, it shows that learning media products based on SAC 3 in the form of android for TLJ subjects for SMK Enrekang Regency students are effective in increasing knowledge/student learning outcomes about Data Communication.